Peran Guru Bimbingan Dan Konseling Dalam Menangani Kasus Ketidakhadiran Siswa Di SMA Negeri 8 Medan, Kec. Medan Area, Kota Medan - Rimma Anisa Siagian; Roslin Naiborhu; Sintia Harianti; Ridha Nababan; Rio Onasis Pangaribuan; Roma Nanda Girsang; Santa A. Murni Situmorang (Pusat Riset dan Inovasi Nasional, 2024)
The problem of student absenteeism is the main problem faced by teachers at SMA Negeri 8 Medan, Kec. Medan Area, Medan City. This problem is caused by several factors, namely internal and external factors. Therefore, the role of educators is needed in efforts to overcome this problem. The aim of the research conducted by the author is to find out the role of guidance and counseling teachers in handling cases of student absenteeism at SMA Negeri 8 Medan, Kec. Medan Area, Medan City. The research method used is descriptive qualitative research. In this research, the author conducted interviews with teachers to obtain information regarding the role of guidance and counseling teachers in handling cases of student absenteeism at SMA Negeri 8 Medan, Kec. Medan Area, Medan City. Interviews are carried out by asking questions that focus on the problem being studied. So, based on research that the author has conducted, the effective and efficient efforts and strategies that guidance and counseling teachers carry out at SMA Negeri 8 Medan are to carry out home visits or direct visits to students' homes and establish good interactive relationships between teachers and students' parents